Use of hazard analysis and critical points to ensure food safety: case study in a fish industry - Sousa, Consuelo Lúcia; Lourenço, Lúcia de Fátima Henriques; LeHalle, Ananda Leão de Carvalho (Brazilian Journal of Production Engineering, 2020)
The system of Hazard Analysis and Critical Control Points (HACCP) seeks the prevention, rationality and specificity to control the risks that a food can offer. The objective of this study was to suggest a HACCP plan for processing line frozen fish fillet in a fish processing company. Were carried out preliminary procedures at plan preparation and implementation of the principles of HACCP. After it was formed the HACCP team was made to the product description, drawn up the flowchart of production and carried out the hazard analysis by the establishment of preventive action. Were identified four Critical Control Points (CCPs) in the flowchart of the process, for which they were established critical limits, corrective actions and monitoring, records and verification procedures. The main preventive action was established to control the temperature for the CCP with a high probability of growth of micro-organisms. The HACCP plan proposed is feasible, however it is necessary to consolidate the implementation of Good Manufacturing Practices (GMP) in the industry and the continuous training of handlers.